THE EMPIRE BUILDER: WAR AND THE SUBJECT OF THE HUMANITIES - Horne, Jenny; Kahana, Jonathan (Surfaces, 1993)
In Carl von Clausewitz's 1832 political treatise On War, the military general is given the form of the humanist scholar. But it isn't until the establishment in the United States of the discipline of the Humanities, between the world wars, that this traditional figure of knowledge is given official discursive status. Using Clausewitz and the rhetoric of the most recent "crisis in the Humanities", we pose the question, "where in fact are our military institutions located?".In order to show the interdependence of these two apparently discrete histories, one would have to redefine modern warfare and humanist scholarship in terms of each other. To this end, we frame the humanist ideals of rational debate, erudition and cultural appreciation, and the production of truth and beauty, as historically linked to the epistemology of war. We address a recent tactical example of this perpetual war — the closing of the humanities department at the University of Minnesota.